Analisis Saluran Pemasaran Ikan Nila di KJA Bina Organik Bersatu Desa Arang Limbung - Pontius Babarona; Josua Parulian Hutajulu; Komariyati Komariyati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
The aim of this research is to analyze the marketing channels and marketing efficiency of tilapia in the Bina Organik Bersatu Floating Net Cage (KJA), Arang Limbung Village. The method used in the research is a descriptive research method with a quantitative approach which quantitative. The data sources used in this research are primary data and secondary data. The location for this research was taken deliberately (purposive), namely in Arang Limbung Village, Sungai Raya District, Kubu Raya Regency, the location selection was carried out deliberately (purposive) with the consideration that KJA Bina Organik Bersatu is one of the fish cultivation businesses that has long been established in Arang Limbung Village. The results of the study indicate that the analysis of tilapia marketing channels in KJA Bina Organik Bersatu, Arang Limbung Village, there are 4(four) marketing channels, namely marketing channel I (producer-consumer), marketing channel II (producer-collector-consumer), marketing channel III (producer-collector-retailer-consumer), and marketing channel IV (producer-retailer-consumer). The marketing efficiency of tilapia in marketing channel I is 0.00, marketing channel II is 6.85%, marketing channel III is 11.78%, and marketing channel IV is 6.23%. These results indicate that marketing channel I is the most efficient because it does not have a marketing institution so there are no costs incurred for marketing.